SME financing innovation and SME development in Bangladesh: an application of ARDL. (2nd November 2019) - Qamruzzaman, Md.; Jianguo, Wei
Abstract : With this study, we try to explore new evidence about financial innovation in small and medium enterprises (SME) financing impact on SME development in Bangladesh from 1985 to 2016. To bring insight, we apply Autoregressive distributed lag (ARDL)-bound testing approach of ascertaining the long-run relationship between financing innovation and SME development, and also investigate directional causality by applying Granger-causality under error correction model. Bound testing confirms the existence of long-run relationship between SME financing innovation and SME development in Bangladesh. Furthermore, Granger-causality test provides evidence to support feedback hypothesis between proxy indicators of financing innovation and SME development both in long-run and short-run. Furthermore, among all control variables, only trade openness confirms unidirectional causality toward SME development in short-run; on the other hand, in long-run, all the variables cause SME development at country level. The study suggests that well-functioned SME financing is a necessary condition but not sufficient to maximize the potential of SME in Bangladesh. So, the government should encourage financial institutions for bringing new ways of SME financing by ensuring cost-effective financial services with a uniform cost structure at large.